Implant placement with inferior alveolar nerve repositioning in the posterior mandible - Kim, Doogyum; Lim, Taeil; Lee, Hyun-Woo; Lee, Baek-Soo; Choi, Byung-Joon; Ohe, Joo Young; Jung, Junho (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2023)
This case report presents inferior alveolar nerve (IAN) repositioning as a viable approach for implant placement in the mandibular molar region, where challenges of severe alveolar bone width and height deficiencies can exist. Two patients requiring implant placement in the right mandibular molar region underwent nerve transposition and lateralization. In both cases, inadequate alveolar bone height above the IAN precluded the use of short implants. The first patient exhibited an overall low alveolar ridge from the anterior to posterior regions, with a complex relationship with adjacent implant bone level and the mental nerve, complicating vertical augmentation. In the second case, although vertical bone resorption was not severe, the high positioning of the IAN within the alveolar bone due to orthognathic surgery raised concerns regarding adequate height of the implant prosthesis. Therefore, instead of onlay bone grafting, nerve transposition and lateralization were employed for implant placement. In both cases, the follow-up results demonstrated successful osseointegration of all implants and complete recovery of postoperative numbness in the lower lip and mentum area. IAN repositioning is a valuable surgical technique that allows implant placement in severely compromised posterior mandibular regions, promoting patient comfort and successful implant placement without permanent IAN damage.